System for interaction, control and remote monitoring of processes, via web, using Java application: virtual weather station - Romero Navarrete, Rommel (2000)
This article develops a robust platform for remote process management.JAVA language is used as a programming language at three levels of development: Control Servers, Web Server and Web Clients. The interaction with the control servers will be through the serial port and/or parallel port depending on the requirement. Thus we can interact with any specialized control device: A microcontroller, a PLC (Programmable Logic Controller), a DSP (Digital Signal Processor) or sophisticated sensors that send data through the aforementioned ports, theLocal network of Control servers ensure the reliability and proper functioning of our processes.The exit door to the Internet will be the "Web Servers", which serve clients; Such a client does not have direct access to the system, until it has verified its privileges. The information thatjourney through the Web is encrypted. Using a microcontroller we will sense: Temperature, humidity,relative ity, wind direction and wind speed. Such information can be monitored from any point on the Internet, likewise our virtual weather station also allows accessto stored data for the respective statistical summary.